Network reconfiguration under normal and fault condition with the presence of distributed generation in a distribution system / Zuhaila Mat Yasin - Mat Yasin, Zuhaila (2008)
This thesis presents the implementation of network reconfiguration in radial distribution system with the presence of distributed generation to improve the distribution system performance in terms of loss minimisation and voltage profile improvement. The network reconfiguration is performed by altering the topological structure of distribution feeders. During normal operating condition, networks are reconfigured to reduce the system real power losses. The optimal sectionalising - tie switch pairs were determined by the TOPO application available in the power system simulation programme for planning, design and analysis of distribution system (PSS/Adept). This application determines optimal sectionalizing - tie switch pairs based on minimum losses configuration and at the same time, all nodes are assured for the supply. The introduction of distributed generation into the distribution system can significantly impact the distribution system depending on the system operating condition, distributed generation characteristic, location and sizing. Therefore, a proper placement plays a very important role. In this thesis, the suitable location for distributed generator was predetermined using the previously developed sensitivity indices derived from voltage stability improvement with respect to changes in injected active and reactive power at a bus. The optimal capacity sizing of the distributed generation was pre-determined using the Evolutionary Programming (EP) optimisation technique. Various locations and sizes of distributed generation were tested in order to realize the effect of location and sizing of distributed generation in terms of loss minimisation and voltage improvement during network reconfiguration. In order to study the effect of location and sizing of distributed generation to the power losses and voltage profile during network reconfiguration for service restoration, a three phase fault is applied at an identified location. The network is reconfigured after the fault is isolated. The study was implemented on the IEEE 69-bus test system. The studies also compare the network performance in terms of loss minimization and voltage profile improvement achieved by optimal network reconfiguration when compensating capacitor present in the system.